1987
DOI: 10.1093/ije/16.1.84
|View full text |Cite
|
Sign up to set email alerts
|

A Seroepidemiological Study of the Prevalence of Hepatitis B Infections in a Hyperendemic New Zealand Community

Abstract: The prevalence of hepatitis B surface antigen (HBsAg) and its antibody (anti-HBs) were studied in 93% of the population of the New Zealand township of Kawerau. Sera were collected from 7901 subjects over six months old, and 3318 (42%) had markers of hepatitis B virus (HBV) infections. Five hundred and nineteen (6.6%) were positive for HBsAg and 485 (96.4%) of 503 retested were confirmed as chronic carriers. HBsAg prevalence was 5.4% in the 0-4 years age group but only 1 of 66 children under one year old was po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The REVEAL study population was exclusively Chinese, while the New Zealand study was 79% Polynesian (Māori and Pacific Islander Peoples). A high proportion of transmission in REVEAL was vertical, while in New Zealand it is predominantly early horizontal, with a sharp increase in the prevalence of exposure to hepatitis B markers in early childhood, and very few children infected under the age of 1 year 24. In Taiwan, the genotype distribution is predominantly B (60%) and C (40%), while New Zealand is predominately C (40%) and D (40%) 25.…”
Section: Objectivementioning
confidence: 99%
“…The REVEAL study population was exclusively Chinese, while the New Zealand study was 79% Polynesian (Māori and Pacific Islander Peoples). A high proportion of transmission in REVEAL was vertical, while in New Zealand it is predominantly early horizontal, with a sharp increase in the prevalence of exposure to hepatitis B markers in early childhood, and very few children infected under the age of 1 year 24. In Taiwan, the genotype distribution is predominantly B (60%) and C (40%), while New Zealand is predominately C (40%) and D (40%) 25.…”
Section: Objectivementioning
confidence: 99%
“…Our studies and published clinical trials with vaccines supplied by manufacturers indicated that good anti-HBs seroconversion rates could be obtained using rDNA vaccines at lower than recommended doses IScheirmann et al., 1987;MiIne et al, 1988b;19891. Nevertheless, it was considered prudent to evaluate the performance of low doses of two licensed commercially available rDNA vaccines in this selected population.…”
Section: Introductionmentioning
confidence: 56%
“…HBV infections are highly endemic in many parts of New Zealand, with the indigenous Maori and the immigrant Pacific Island groups most seriously affected IBoveington, 1972;Milne et al, 1987;Tobias et al, 19871. At present, all newborn and preschool (0-4 years old) children are offered State-funded protective immunisation against HBV.…”
Section: Introductionmentioning
confidence: 99%
“…Babies of carrier mothers who escape infection at birth are at increased risk of becoming infected by their mothers or other carriers in the family or school in the first decade of life [15]. The higher HBsAg carrier rate in boys may be due to the types of play engaged by boys and specific opportunities to exchange contaminated blood in the family or in the school [16,17].…”
Section: Discussionmentioning
confidence: 99%